Selected speeches - Akunyili, Dora Nkem (Lagos: Prestige Books, 2010)
The book is a compendium of the speeches made by prof. Dora Nkem Akunyili the former Director General of NAFDAC between April 2001 and December, 2008.The speeches were delivered at different for a to different persons groups, bodies and associations related to NAFDAC regulated products. The audience included the Nigerian general public, government officials, law enforcement agents, the press, dealers and stakeholders religious leaders.
Includes bibliographical references.
lje 11/9/13 , ijb 29/04/2019
Loans
Keywords: Drug control; Pharmaceutical industry; National Agency for Food and Drug Administration and Control (NAFDAC)